Effects of acetate administration on endurance training-induced metabolic adaptations in mice fed high fat diet - Kohei Seike; Mai Banjo; Suguru Nakano; Yumiko Takahashi; Kenya Takahashi; Shoko Abe; Hideo Hatta (Japanese Society of Physical Fitness and Sports Medicine, 2020)
We investigated the effects of chronic pre-exercise acetate administration on body weight and metabolic adaptations to endurance training in ICR mice fed with either a normal fat diet (NFD) or high fat diet (HFD), respectively. Mice were divided into a control group (Con), an acetate group (Ace), a training group (Tra), and an acetate+training group (Ace+Tra) with NFD or HFD, respectively. Mice received orally either water or acetate (72 mg/kg body weight/day) for 4 weeks. The mice in the training group were subjected to training using a treadmill (20-25 m/min×60 min, 5 times/week) immediately after administration. As a result, in the NFD mice, there was no effect of acetate in any of the measurements. In the HFD mice, the final body weight in the Ace, Tra and Ace+Tra groups was significantly lower than the Con group. Moreover, the acetate treatment tended to decrease blood glucose concentration at rest. Gastrocnemius muscle glycogen concentration in the Ace+Tra group was significantly higher than that of the Ace and Tra groups. Unexpectedly, a significant negative main effect of acetate treatment in the maximal activity of β-HAD was observed, though the endurance training increased enzyme activity of citrate synthase in the plantaris muscle. These findings show the possibility that acetate treatment with endurance training shifts the metabolic characteristics of mice toward a carbohydrate metabolism against a lipid metabolism with the HFD condition, but not with the NFD condition.